The river why eaudiobook - Duncan, David James (2017)
The classic novel of fly fishing and spirituality republished with a new Afterword by the author. Since its publication in 1983, The River Why has become a classic. David James Duncan's sweeping novel is a coming-of-age comedy about love, nature, and the quest for self-discovery, written in a voice as distinct and powerful as any in American letters. Gus Orviston is a young fly fisherman who leaves behind his comically schizoid family to find his own path. Taking refuge in a remote cabin, he sets out in pursuit of the Pacific Northwest's elusive steelhead. But what begins as a physical quarry becomes a spiritual one as his quest for self-knowledge batters him with unforeseeable experiences. Profoundly reflective about our connection to nature and to one another, The River Why is also a comedic rollercoaster. Like Gus, the reader emerges utterly changed, stripped bare by the journey Duncan so expertly navigates.